Hak Cipta sebagai Jaminan (Agunan) dalam Jaminan Kredit di Perbankan - Pratama, Nendyanata Anugrah; Primananda A, Tahegga (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The creative industry in Indonesia has experienced significant growth over the past few years. All works produced within this sector are protected under the intellectual property regime, particularly Copyright, as a form of legal protection for the creative outputs of individuals or groups. Nevertheless, the majority of creative economy actors, especially small- and medium-scale enterprises, continue to encounter substantial constraints in accessing financing. Intangible assets, such as Copyright, are not yet widely understood or recognized by financial institutions, particularly banks, as acceptable collateral for credit facilities. In fact, Copyright possesses tangible economic value, including income derived from royalties, licensing arrangements, and exclusive contracts, which may serve as a legitimate basis for assessing creditworthiness. Indonesian banking institutions have a principal function as collectors and distributors of public funds, as stipulated in Article 3 of Law Number 10 of 1998 concerning Banking. In providing credit to customers, banks are required to apply the prudential Principle, commonly known as the 5C Principle, which consists of Character, Capacity, Capital, Collateral, and Condition of the Economy. One form of security interest recognized under Indonesian law is fiduciary security, which may be imposed upon movable property, whether tangible or intangible, as well as upon specific immovable property other than those eligible to be encumbered with mortgage rights, as provided in Article 1, point 2 of Law Number 42 of 1999 concerning Fiduciary Security. Copyright constitutes one category of property that may be pledged as an object of fiduciary security pursuant to Article 16 paragraph (3) of Law Number 28 of 2014 concerning Copyright. Accordingly, based on these statutory provisions, Copyright should, in Principle, be eligible to serve as collateral for bank credit. However, in practice, banking institutions remain reluctant to accept Copyright as credit collateral for various reasons.